Insights into real cotton-textile dyeing wastewater treatment using solar advanced oxidation processes - Petrick A. Soares (2014)
Different advanced oxidation processes (AOPs) were applied to the treatment of a real cotton-textile dyeing wastewater as a pre-oxidation step to enhance the biodegradability of the recalcitrant compounds, which can be further oxidized using a biological process. Tests were conducted on a lab-scale prototype using artificial solar radiation and at pilot scale with compound parabolic collectors using natural solar radiation. The cotton-textile dyeing wastewater presents a lilac color, with a maximum absorbance peak at 641 nm, alkaline pH (pH = 8.2), moderate organic content (DOC = 152 mg C L-1, COD = 684 mg O-2 L-1) and low-moderate biodegradability (40 % after 28 days in Zahn-Wellens test). All the tested processes contributed to an effective decolorization and mineralization, but the most efficient process was the solar-photo-Fenton with an optimum catalyst concentration of 60 mg Fe2+ L-1, leading to 98.5 % decolorization and 85.5 % mineralization after less than 0.1 and 5.8 kJ(UV) L-1, respectively. In order to achieve a final wastewater with a COD below 250 mg O-2 L-1 (discharge limit into water bodies imposed by the Portuguese Legislation-Portaria no. 423/97 of 25 June 1997), considering the combination of a solar-photo-Fenton reaction with a biological process, the phototreatment energy required is 0.5 kJ(UV) L-1, consuming 7.5 mM hydrogen peroxide, resulting in 58.4 % of mineralization (t(30W) = 3.2 min; (T) over bar = 30.7 degrees C;(pH) over bar = 2.80; (UV) over bar (G,n) = 13 W m(-2)).